A Nitrogen budget for Norway analysis of Nitrogen flows from societal and natural sources (1961-2020). - Martin F Hohmann-Marriott (PLoS ONE)
Nitrogen is a chemical element that is cycled through Earth's lithosphere, hydrosphere, cryosphere and atmosphere, as well as a crucial component of the molecular machinery of life. Being an intrinsic part of the biosphere, the flow of nitrogen in a country can provide unique insights into the sustainability of a society. This study investigates how nitrogen is used in Norway between 1961 and 2020. Nitrogen inputs from atmospheric deposition, biological nitrogen fixation and from weathering, as well as from synthetic fertilizers are addressed. These sources of nitrogen are used by plants that form the basis of agriculture and forestry. Nitrogen, in the form of protein, is imported to sustain the Norwegian population and the production of animals in agriculture and fisheries. Agricultural livestock is used almost exclusively for domestic consumption, while fish captured and raised in aquaculture are the main sources of exported food. Even though petroleum and wood contain only a small proportion of nitrogen, due to the traded volume, a large amount of nitrogen contained in these goods is exported. Nitrogen is lost through sewage and manure leaching, as well as atmospheric emissions. These emissions are mostly in the form of nitrogen oxides and ammonia, which are released by burning fossil fuels and metabolizing animals, respectively.